Temperature regime influences accessions and effectiveness of germination promoters in the high-Andean crop maca - Valqui-Peña D. (2021)
This work was supported by the Fondo Nacional de Desarrollo Cient?fico, Tecnol?gico y de Innovaci?n Tecnol?gica (FONDECYT-PERU) under Grant 190-2015-FONDECYT-DE which provided a fellowship for David Valqui-Pe?a. We thank Mois?s Alderete, Arturo C?rdenas, and Efra?n Z??iga for providing the seed accessions of maca. We are also grateful to Ang?lica P?rez, Jonhny V?lchez, Ovaldo Rojas, and Fluber Mamani, as well as the ?Asociaci?n de Productores Agropecuarios Org?nicos de Carhuamayo? for generously sharing their knowledge on this crop. Finally, we thank Cristina Guerra-Giraldez for proofreading the?manuscript.